Slippery Stents: A Case Report and Review of the Literature Describing Patients with May-Thurner Syndrome That Experienced Stent Migration - Ramy Mando; Priscilla Sigua-Arce; Lisa Spencer; Alexandra Halalau (Case Reports in Vascular Medicine)
Endovascular stent placement is an effective treatment for relieving chronic venous obstruction in patients with May-Thurner Syndrome (MTS) with or without the presence of thrombotic lesions. Stent migration is a rare but potentially life-threatening complication of endovascular stenting. Herein, we describe a case of stent migration from the left common iliac vein into the right heart, requiring open-heart surgery. We also completed a literature review of MTS patients with stent migration in hopes of raising awareness of this rare and life-threatening complication.